Triagem de carboidratos de reserva de espécies herbáceas dos campos rupestres da serra dourada (GO) e análise da distribuição temporal de frutanos em dimerostemma vestitum (baker) sf blake (asteraceae) - Silva, Taiza Moura (2014)
The fructans are soluble carbohydrates comprised of fructose residues linked to a sucrose molecule to form linear or branched polymers. The fructan accumulating families are more common in environments subject to abiotic stresses such as cold and drought, and suggested that fructans act like osmotic regulators and membrane stabilizers, increasing the tolerance of species to environmental stresses. In Cerrado species fructans are accumulated in underground reserve organs and are mobilized when energy is needed, being sources of energy and carbon for intensive periods of growth as sprouting and flowering. Due to economic and adaptive significance of fructans, this study aimed to perform a screening of carbohydrates in reserve organs of Cerrado species and analyze the occurrence of seasonality in the content and composition of fructans in the selected species Dimerostemma vestitum (Baker) SF Blake (Asteraceae). In addition, we aimed at providing information about the morpho-physiology of the vegetative organs of this species. Eight herbaceous species of rocky savannas were analyzed. Chrisolaena simplex (Less.) Dematt, Chromolaena squalida (DC.) R.M.King & H.Rob., Aspilia foliacea (DC.) R.M.King & H.Rob. and Dimerostemma vestitum (Baker) SF Blake accumulate inulin-type fructans. In Lippia lupulina Cham. and Justicia asclepiada (Nees) Wassh. & C.Ezcurra (Acanthaceae) was confirmed the presence of raffinose as a reserve carbohydrate, getting uncertain in Hyptis remota Pohl ex Benth (Lamiaceae) and Evolvulus pterocaulon Moric. (Convolvulaceae) the type of carbohydrate stored. D. vestitum displayed a seasonal cycle with dormancy during the dry season, and sprouting, flowering and fruiting during the rainy season. The content of fructo- polysaccharides decreased with increase of fructo-oligosaccharides in phases of intense energy use, as a result of their mobilization during high demand of energy. D. vestitum accumulates inulin-type fructans, with average degree of polymerization between 18 and 35. The morpho-anatomical adaptations of D. vestitum to rocky savannas are related mainly to the presence of xylopodium, a rigid structure, with a number of buds and mixed anatomical nature, that accumulates water and reserve compounds such as fructans. In addition, stem and leaf morpho-anatomical adaptive features possibly contribute to the survival and development of this species in the rocky fields.